Operational procedure of sea-freight department and recruitment and selection process of Kuehne + Nagel Bangladesh Limited - Farzana, Nafisa (BRAC University, 2018)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2018.